Vanya on 42nd Street [videorecording (DVD)] - Malle, Louis, 1932-1995; Gregory, André; Gregory, André; Shawn, Wallace; Moore, Julianne; Smith, Brooke, 1967-; Gaynes, George; Chekhov, Anton Pavlovich, 1860-1904 (Criterion collection, 2012)
A group of actors meet to rehearse Chekhov's Uncle Vanya and find the same conflicts in their own lives as are dealt with in the play.